FORMALIN FIXATION AT LOW TEMPERATURE PROVIDES BETTER YIELD AND INTEGRITY OF DNA - Makulović, Stefan D; Vitošević, Katarina M; Slović, Živana S; Todorović, Miloš S; Todorović, Danijela (Medicinski podmladak, 2019)
Introduction: Fixation with formalin, a widely used procedure to preserve tissue samples, leads to damage of DNA through crosslinking activity. The factors that could influence the fixation and integrity of DNA may be numerous: incubation time, tissue type, concentration of formalin, temperature, pH and viscosity. Aim: The aim of this investigation was to examine the influence of incubation time and temperature of formalin fixation on the yield, purity and integrity of DNA isolated from healthy human heart myocardial tissue taken during medico-legal autopsy. Material and methods: Heart tissue samples were fixed in phosphate-buffered formalin at +4°C in the dark, as well as at room temperature in the presence of light. The DNA was isolated after one day, then successively every day during the first week, and then on the tenth day, and after two and four-week periods using phenol-chloroform-isoamyl alcohol extraction method. The absorbances were measured at 260 nm and 280 nm, which allows calculation of yield and purity of nucleic acid in the samples. The PCR amplification of two genes, GPDH (150 bp) and ß-actin (262 bp), were performed to evaluate the degree of DNA molecule fragmentation. Results: The highest yield, purity and preserved integrity of DNA were obtained from the samples fixed in formalin at +4°C in the darkness. In these samples, GPDH and ß-actin genes were amplified up to 14 days, unlike the samples that were fixed at the room temperature in which the ß-actin gene was amplified up to 5 days, while the GPDH gene fragment was successfully amplified up to 10 days of fixation. Conclusion: The temperature, presence of light and the incubation time of formalin fixation all have important influences on yield, purity and integrity of DNA during the fixation process.